Copper-coated urea for rice production. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2004)
Urea is an important fertilizer-N source used in rice production in the world today. However the efficiency of urea is low because it is easily hydrolyzed and lost through ammonia volatilization. Reducing urea solubility and the rate of hydrolysis can increase urea efficiency. Slow release urea fertilizers can minimize the loss. Recent field investigations showed that there are Cu deficiencies occuring in many sites in the rice growing area in the Muda Irrigation Scheme, Kedah.